Bank Customer Protection Law from Skimming Crimes: According to The Consumer Law and The Banking Law - Fajriansyah Anugraha; Hanifah Febriani (Proceeding International Conference Restructuring and Transforming Law, 2023)
The purpose of this article is to explain the legal protection and responsibility of banks for the security of customers' personal data and customer deposits at the bank in cases of skimming crimes. This research uses a juridical-normative approach, namelyby researching library materials, namely primary and secondary legal materials. Data collection was carried out through literature study. The results of this research indicate that the bank is responsible for losses experienced by customers due to theft using the skimming crime mode, if proven by CCTV cameras and there is no negligence on the part of the customer who is the victim. Legal protection for customers is related to the reporting obligations offered by banks, namely Law no. 8 of 1999 concerning Consumer Protection and PBI no. 16/1/PBI/2014.